Fede e ragione nel Monologion e nel "Proslogion" di sant’Anselmo - Aguilar LC, Alfonso (Alpha Omega, 2010)
Today’s clash between faith and reason end up in fideism and rationalism. An accurate study of Saint Anselm’s works can offer us hints to attain the urgent reconciliation of faith and reason in a new way. In the Monologion and Proslogion a series of key principles and attitudes are advanced: placing God as the main aim of all human research (quaerere Deum), forging a right will and the righteousness of the will, keeping the harmony between faith and reason against all forms of fideism and rationalism, giving priority to a loving and reasonable faith over reason, trusting in the power of reason, humbly acknowledging the limits of reason, and taking the intellectus fidei as the necessary bridge between faith and the vision of God and of the truth.